(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Tragia involucrata Linn is traditionally utilized in Indian medicine for various ailments. This study evaluates its phytochemical profile, investigates the in silico interactions of major bioactive compounds against acetylcholinesterase (AChE), and assesses its in vitro neuro- cytocompatibility on human neuroblastoma (SH-SY5Y) cells. Methods: Ethanolic leaf extract of T. involucrata underwent preliminary phytochemical screening and GC-MS profiling. Key identified phytoconstituents phytol, neophytadiene, methyl palmitate, ethyl linolenate, and squalene were docked against AChE. Neurocompatibility was determined via MTT assay on SH-SY5Y cells treated with extract concentrations ranging from 12.5 to 200 μg/mL for 24 hours. Preliminary screening confirmed the presence of alkaloids, flavonoids, tannins, saponins, glycosides, phenolics, steroids, and triterpenoids. In silico molecular docking demonstrated stable binding configurations and high binding affinities of the selected ligands within the active site of AChE. In vitro biological evaluation verified excellent cytocompatibility, as SH-SY5Y cell viability remained exceptionally high, ranging from 99.73% at 12.5 μg/mL to 96.33% at the maximum dose of 200 μg/mL after 24 hours. No acute cytotoxic effects were observed, and the half-maximal inhibitory concentration (IC 50) was not applicable (N/A). The leaf extract of T. involucrata exhibits a rich phytoconstituent profile, potent theoretical anti-AChE activity, and remarkable neuro-cytocompatibility. These findings substantiate its safety and therapeutic potential, laying a solid foundation for further research in neurodegenerative disease management.